The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.anplas.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism events after breast reconstructions with DIEP free flaps in 192 consecutive case

Abstract: Our data confirm that the Caprini RAM is a valuable assessment tool for VTE risk measurement among all patients undergoing autologous breast reconstruction. As most candidates for DIEP flap belong to the high-risk group, combined anticoagulation prophylaxis methods are required for most cases, particularly chemoprophylaxis up to four weeks postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…Although this difference did not reach statistical significance, our study’s 1.5% risk is lower than the historical more than 3% rate that has been found in other studies for breast reconstruction patients only receiving prophylaxis while in-house. 11 , 13 A recent retrospective review reported a VTE rate among microsurgical breast reconstruction patients as 1.3%, similar to our findings. However, specific chemoprophylaxis regimens were not assessed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although this difference did not reach statistical significance, our study’s 1.5% risk is lower than the historical more than 3% rate that has been found in other studies for breast reconstruction patients only receiving prophylaxis while in-house. 11 , 13 A recent retrospective review reported a VTE rate among microsurgical breast reconstruction patients as 1.3%, similar to our findings. However, specific chemoprophylaxis regimens were not assessed.…”
Section: Discussionsupporting
confidence: 91%
“…VTE risk was assessed using the 2005 Caprini model for VTE which stratified patients into “very low” (0 points), “low” (1–2 points), “moderate” (3–4 points), and “high” (≥5 points) risk categories based upon ACCP guidelines. 2 , 11 …”
Section: Methodsmentioning
confidence: 99%
“…Hospitalised patients have an increased risk of venous thromboembolic events (VTE) and the use of chemoprophylaxis in patients undergoing autologous reconstruction is well established. 36 The risk of a VTE for abdominal-based reconstructions is estimated to be around 2%-5% 37 but appears much lower for implant-based reconstructions. 38 COVID-19 appears paradoxically both to increase the risk of VTE and also of bleeding due to hepatic dysfunction.…”
Section: Clotting Complicationsmentioning
confidence: 99%
“…Modarressi et al found a 3.1% incidence in 192 DIEP flap patients, while Sultan et al reported a 6.8% rate after 133 abdominally based free flaps, including 68 DIEP flaps. 10,14 Both studies had a patient population with an average Caprini score (5.7 and 6.0, respectively) comparable to our cohort's average (6.0; range, 2-10). The lowest VTE incidence in literature was found in Guerra et al's study, which reported a 0.8% rate in 140 bilateral DIEP flaps.…”
Section: Discussionmentioning
confidence: 64%